1989
DOI: 10.3758/bf03205220
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of several retrieval cues over time: Evidence for time-dependent reorganization of memory

Abstract: The retention performance following partial training (15 trials) of a brightness-discrimination avoidance task has been shown to fluctuate over time, with a drop in performance 1 h after training (Kamin effect), a long-term spontaneous improvement (LTSl) after 3 days, and long-term spontaneous forgetting after 21 days. The purpose of this paper was to determine ifthese time-dependent modulations of retention performance reflect time-dependent modifications in the organization of the attributes that constitute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 39 publications
3
21
1
Order By: Relevance
“…These experiments demonstrated that electrical stimulation of the area shortly before testing again demonstrated a significant reduction in errors in the maze (Sara and Devauges 1988) Several experiments have indicated that a short exposure to specific features of the training episode can compensate for the disruption due to long-term forgetting (Spear and Parsons 1976;Spear et al 1980). The experimental context seems to be a particularly effective reminder to alleviate performance disruption due to longterm forgetting in rats trained in an appetitive or in an aversive discrimination task (Deweer et al 1980;Gisquet-Verrier et al 1989). In these studies, the improvement resulting from the pretest exposure to the retrieval cues is evidenced shortly thereafter (from 0 to 10 min) and is not maintained over time (Gisquet-Verrier 2009).…”
Section: Memory Reactivation Alleviates or Reverses Performance Disrumentioning
confidence: 99%
“…These experiments demonstrated that electrical stimulation of the area shortly before testing again demonstrated a significant reduction in errors in the maze (Sara and Devauges 1988) Several experiments have indicated that a short exposure to specific features of the training episode can compensate for the disruption due to long-term forgetting (Spear and Parsons 1976;Spear et al 1980). The experimental context seems to be a particularly effective reminder to alleviate performance disruption due to longterm forgetting in rats trained in an appetitive or in an aversive discrimination task (Deweer et al 1980;Gisquet-Verrier et al 1989). In these studies, the improvement resulting from the pretest exposure to the retrieval cues is evidenced shortly thereafter (from 0 to 10 min) and is not maintained over time (Gisquet-Verrier 2009).…”
Section: Memory Reactivation Alleviates or Reverses Performance Disrumentioning
confidence: 99%
“…Pretest exposure to the experimental context in which discriminative avoidance training had taken place also alleviates forgetting. These experiments compared the effectiveness of the contextual cue and the conditioned stimulus (CS) as reminders and found that pretest priming with the CS facilitated performance at short training to test intervals, whereas the contextual cue was only effective after a long retention interval, when control animals showed considerable forgetting (Gisquet-Verrier and Alexinsky 1986;Gisquet-Verrier et al 1989). (Left) Number of errors at each daily trial during acquisition; (right) retention performance of rats tested 3 weeks after the last training trial.…”
Section: Memory Retrieval Facilitation After Forgetting: Contextual Cmentioning
confidence: 99%
“…The cuing procedure has been widely used in a variety of paradigms, and it still appears to be effective at very long delays after learning (Dekeyne, Deweer, & Sara, 1987;Gatti, Pais, & Weeks, 1975;Gisquet-Verrier, Dekeyne, & Alexinsky, 1989). Thus, it is possible for cuing to reactivate even a longestablished memory.…”
mentioning
confidence: 99%